Could the systemic immune-inflammation index be a new biomarker of inflammation in children with asthma? - Omer Okuyan; Seyma Dumur; Yusuf Elgormus; Hafize Uzun (Medicine Science)
Asthma is a disease with a complex etiology that is caused by genetic and environmental factors. More recently, the importance of changes related to the systemic immune-inflammation (SII) index has been recognized. The aim of this study was to investigate SII as a potential novel biomarker of the inflammatory process in children with asthma. This study included 60 children hospitalized with asthma exacerbation between February and September 2021. Complete blood counts of the patient group were obtained during the exacerbation period and during the asymptomatic period of 3 months after exacerbation. Furthermore, SII, C-reactive protein (CRP), eosinophil-to-lymphocyte ratio (ELR), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) values were compared in both periods. All values of the patient groups were compared with the healthy control group (n=60). CRP, SII, NLR and ELR levels were significantly higher in the asymptomatic period compared to the control group (All of them, p [Med-Science 2025; 14(1.000): 81-4]